2020
DOI: 10.1186/s12864-020-6677-y
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing of Puccinia striiformis f. sp. tritici mutant isolates identifies avirulence gene candidates

Abstract: Background: The stripe rust pathogen, Puccinia striiformis f. sp. tritici (Pst), threats world wheat production. Resistance to Pst is often overcome by pathogen virulence changes, but the mechanisms of variation are not clearly understood. To determine the role of mutation in Pst virulence changes, in previous studies 30 mutant isolates were developed from a least virulent isolate using ethyl methanesulfonate (EMS) mutagenesis and phenotyped for virulence changes. The progenitor isolate was sequenced, assemble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 87 publications
2
27
0
Order By: Relevance
“…However, race evolution and pathogenicity behavior are less explored. These unsolved issues provoked scientists and diverted their attention toward sequencing of the Pst genome to provide a deep insight into pathogenicity and host–pathogen interaction ( 10 ). To date, more than 15 Pst reference genomes are publicly available ( 11 ).…”
Section: The Pst Pathogenmentioning
confidence: 99%
“…However, race evolution and pathogenicity behavior are less explored. These unsolved issues provoked scientists and diverted their attention toward sequencing of the Pst genome to provide a deep insight into pathogenicity and host–pathogen interaction ( 10 ). To date, more than 15 Pst reference genomes are publicly available ( 11 ).…”
Section: The Pst Pathogenmentioning
confidence: 99%
“…Given the complexity of fungal genomes and the limited knowledge of the genetic mechanisms underlying the development of virulence in fungal pathogens, more and more integrated approaches have been developed for effector detection. One such integrated approach is to combine genome-wide association analysis with variant comparisons, such as our study on AvrLr20 mining [23], a previous study on AvrPm3 in powdery mildew [63], and a recent study using 30 Pst isolates derived from ethyl methanesulfonate mutagenesis [21]. Although these association analyses still focus on genomic variations at the level of SNPs and InDels, our study is the first to integrate the major type of structure variation, CNV, into comparative analysis at the genome-wide scale in a rust pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…tritici (Pst) [18]. With the availability of reference genomes, advances have been made for all three wheat rust fungi in genome-wide studies for effector mining, including studies on Pst [19][20][21], Pgt [22], and Pt [23], which have detected a panel of candidate avirulence genes for functional validation. One earlier study identified 15 candidates for 14 Avr genes using gene expression and RNA SNP analysis [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Salcedo et al obtained stripe rust mutants through EMS-induced mutation and performed genome sequencing to obtain AvrSr35 candidate genes, and then veri ed the candidate genes through co-expression of AvrSr35 and its corresponding resistance gene in tobacco and wheat to trigger cell death [8]. Li et al screened 30 mutant variants from the least virulent isolate generated by EMS mutagenesis and candidates Avr genes were determined by sequencing [9]. Transcriptomics has proven to be an instrumental molecular tool to help identify virulence effectors and Avr genes [10][11][12].…”
Section: Introductionmentioning
confidence: 99%